Withdrawal of artificial nutrition and hydration in the Neonatal Intensive Care Unit: parental perspectives. Issue 1 (23rd March 2012) - Hellmann, Jonathan; Williams, Constance; Ives-Baine, Lori; Shah, Prakesh S
Abstract : Objective: To review the experience of the practice of withdrawal of artificial nutrition and hydration (WANH) and to describe parental perspectives on the process. Design: A retrospective chart review and parental survey. Setting: Tertiary level Neonatal Intensive Care Unit (NICU). Participants: Infants who had WANH after withdrawal of other life-sustaining treatment, and their parents. Main outcome measure: Parental perspectives on the care and process were obtained through a survey administered 1 to 4 years after the death of their infant. Results: Fifteen cases (5.5% of all mortality and 0.5% of all admissions) of WANH were identified, and 10 parents participated in the survey. The median (range) gestational age was 40 weeks (31–42) and birth weight was 3409 g (2000–4640). The reason for WANH was predicted poor outcome due to severe neurological injury/disease. The median (range) time between WANH and death was 16 days (2–37). All parents reported favourable perceptions of preparation, support, communication and care. Seven parents reported concerns regarding pain experienced by their infant. Parents reported the ability to spend quality time, creating tangible memories and the virtues and professional qualities of the caregivers to be helpful, but identified that consistency and continuity of care could be improved. Conclusion: Within the spectrum of palliative care in neonates, WANH can be a tenable, justifiable and humane practice in the NICU.